O valor da imagem e do corpo na Ética de Espinosa - Souza, Angeliana Patrícia de (2022)
This dissertation aims to reflect on the value of the imaginative idea in structuring human knowledge according to Spinoza's Ethics. From a critical perspective, Spinoza breaks with the scholastic vision of Christian philosophy that separated mind and body, overvaluing the former to the detriment of the latter. In the tension between the "individual" (Body) and the "universal" (Mind), the author elucidates the way in which the Body participates in the constitution of knowledge from the partial apprehension of things in experience, due to the common order of nature in which it has access to effects. When evaluating the value of imaginative knowledge in shaping the passage to rational knowledge it turns out that the teachings of the first level of knowledge must not only not be eliminated, but must be reconsidered from a new viewpoint. For, thanks to it, one passes from the level of the "natural course" (nature's common order) to its rational level. Because of this the first phase of knowledge, based exclusively on the body, has to be elucidated from the body's apprehension of things in experience. Only from the Body can there be knowledge of self and external things, uniting the necessity of practice in experience and theory in rational and intuitive knowledge of things. Therefore, starting from the Body is that the subject will advance up steps, avoiding being hostage of the basic equivocation of representing the formation of ideas solely by the mind, without the participation of the Body.